Restoring silvopastures with oak saplings: effects of mulch and diameter class on survival, growth, and annual leaf-nutrient patterns - Jiménez, M. N.; Pinto, J. R.; Ripoll, M. A.; Sanchez-Miranda, A.; Navarro, F. B. (Agroforestry Systems, 2014)
In Southwestern Spain, multifunctional silvopastoral systems consisting of pastureland and open oak woodlands are known as Dehesas. These, and other similar systems of the Mediterranean basin, are currently threatened by increasing intensive land use. As a consequence, oak regeneration is declining and is in need of adequate management and active restoration. Traditional restoration practices outplant one-year-old, nursery-produced oak seedlings grown in 250–350 cm3 containers, but establishment and growth results are typically poor. This work examines holm oak (Quercus ilex L. subsp. ballota (Desf.) Samp.) grown in a non-conventional container size (24 l) and age (6–7 years) with three mulch treatments (control, stone, and straw). In an open Dehesa of SE Spain, 106 oak saplings were planted in March 2010, and survival, diameter at breast height (DBH), and leaf-nutrient concentrations were analyzed. Forty months after planting, all treatments showed high survival (81 %) but only straw-mulched saplings differed significantly (94 %) from control (74 %). DBH increased over time but showed no significant differences among mulch treatments. Saplings with high initial DBH showed the greatest growth and change in DBH at the end of the study period. Leaf- nutrient concentrations changed significantly in the year following outplanting. Bi-monthly foliar nutrient concentration data show decreases in P, K, Zn, and B and sharp increases in Ca and Fe. In this work, we provide some evidence concerning the viability of non-conventional oak size for restoring, regenerating, or building up new agroforestry or silvopastoral systems. A combination of saplings with more than 10 mm of DBH and straw mulch is recommended.
Keywords: 10; 1007; ballota á saplings á; contains supple-; DBH; Dehesa; dehesa á mulch á; doi; electronic supplementary material the; Mulch; online version of; quercus ilex subsp; quercus ilex subsp. ballota; s10457-014-9737-y; Saplings; semi-arid; semi-arid á dbh á; Spain; this article

Influence of different post-planting treatments on the development in Holm oak afforestation - Jiménez, M. N.; Fernández-Ondoño, E.; Ripoll, M. A.; Navarro, F. B.; Gallego, E.; De Simón, E.; Lallena, a. M.; Simón, E; Lallena, a. M. (Trees, 2007)
This work examines the inﬂuence of different post-planting treatments in the development of afforested Holm oak, Quercus ilex L. subsp. ballota (Desf.) Samp., in an abandoned agricultural ﬁeld in SE Spain. A total of nine post-planting treatments were carried out: tilling spring and autumn in different years, spreading of organic and inorganic mulch, irrigation in different periods. Soil preparation prior to planting consisted of digging of a hole with a backhoe excavator of 80 HP and homogenized the proﬁle characteristics. Survival, nutrient concentrations in both leaves and soil, and foliage surface have been studied. Dryseason irrigation every 2 weeks provided the best survival rate (98.3%), while mulching with solid urban wastes caused the worst results (6.6%). The supply of forest debris increased the N, K, and Mn concentrations at all depths with respect to the other treatments, and the solid urban waste had the same effect in N, P, K, Na, Cu, Fe, and Zn. All the foliar nutrients decreased in 2005 with respect to the 2004 sampling, except in N, Cu, and Zn. The use of foliar nutrient concentrations, together with the increase in leaf surface is proposed as a non-destructive index of development and of forestation stands in the ﬁrst stages of growth. The application of forest debris, and particularly the placement of boulders in the beds of individual trees proved most effective in sapling development.
Keywords: á; á semi-arid; Afforestation; afforestation á post-planting treatments; Holm oak; holm oak á nutrients; Nutrients; Post-planting treatments; semi-arid

Modificación del microclima edáfico producido por riegos en forestaciones de zonas semiáridas - Jiménez, M. N.; Ripoll, M. A.; Navarro, F. B. (Investigación agraria. Sistemas y recursos forestales, 2004)
In this work, we analyse the effect that the irrigation carried out in different times during the summer drought produces on the edaphic microclimate over holm oak plants (Quercus rotundifolia) in abandoned agricultural soils of continental semiarid climate. The study has been done over 5 plots of 60 plants each, located in the high plateaux of Rambla Becerra (Guadix-Granada), in which it has been accomplished a continuation of the survival rate and development after the planting during two years (2001-2002). The answer of the plant to its new medium was excellent in all the irrigated plots, whereas in the witness plot (without irrigation) the survival is considerably inferior. The height of the holm oaks in those plots with any kind of irrigation is significantly superior than the ones in the witness plot, and the diameter of the holm oaks of the plots which receive continuous summer irrigation shows significant differences with respect to the rest of the plots. The bioclimatic diagrams achieved in each plot reflect relevant differences; the summer irrigation reaches to reduce the drought period and even, in the plot that receives the continuous summer irrigation, this is eradicated, thus generating a new period of vegetation activity. The humidity of the soil shows significant differences, being the plot number 8, which is continually being irrigated, the only one that keeps the humidity in depth. The hydric deficit diminishes punctually in the plots irrigated only once, whereas in the parcel n. 8 diminishes drastically with the following increase in the vegetation activity.
Keywords: agricultural; bioclimatic diagrams; humidity; microclimate; Soil